IMPLEMENTASI KEBIJAKAN PROGRAM GOJEK SAMPAH PLASTIK (GOTIK) DALAM UPAYA MENANGGULANGI KEBERADAAN SAMPAH PLASTIK MELALUI PARTISIPASI MASYARAKAT DI KECAMATAN KUTA UTARA, KABUPATEN BADUNG - Saputra, I Gede Made Okta; Winaya, I Ketut; Wijaya, Komang Adi Sastra (CITIZEN CHARTER, 2023)
The goal of this research is to analyze the application of the Gojek Plastic Waste (GOTIK) program policy in a determination to overcome the presence of plastic waste through community participation in North Kuta District, Badung Regency. The researcher employed documentation, interviews, and observation as the data collection in this descriptive qualitative research. The findings illustrate the implementation of the Gojek Program for Plastic Waste (Gotik) in North Kuta District, there were 4 important items, namely 1) Communication, communication between organizations and implementing activities in the Implementation of the Gojek Program for Plastic Waste (Gotik) carried out several strategies, some of which were by preparing the apparatus who is responsible for each existing field and has carried out several socializations to customers. 2) Resources, resources are very important in managing waste as well as in carrying out several activities in the waste bank. 3) Disposition, policy implementation in order to achieve maximum success must be identified and the characteristics of the implementing agent known. 4) Bureaucratic structure, the division of tasks in the UPTD section is well structured and the community has significance influence in the application of the central waste bank. The obstacle encountered is that not all people want to participate in running the Gojek Program for Plastic Waste (Gotik) other than because people do not want to sort their waste, which makes the income of the waste bank decrease. Keywords: implementation, plastic waste, participation